Growth of ZnO Nanorods on Stainless Steel Wire Using Chemical Vapour Deposition and Their Photocatalytic Activity - Siti Nor Qurratu Aini Abd Aziz; Swee-Yong Pung; Nurul Najiah Ramli; Zainovia Lockman (The Scientific World Journal)
The photodegradation efficiency of ZnO nanoparticles in removal of organic pollutants deteriorates over time as a high percentage of the nanoparticles can be drained away by water during the wastewater treatment. This problem can be solved by growing the ZnO nanorods on stainless steel wire. In this work, ZnO nanorods were successfully grown on stainless steel wire by chemical vapour deposition. The SAED analysis indicates that ZnO nanorod is a single crystal and is preferentially grown in [0001] direction. The deconvoluted O 1s peak at 531.5 eV in XPS analysis is associated with oxygen deficient, revealing that the ZnO nanorods contain many oxygen vacancies. This observation is further supported by the finding of the small Iuv/Ivis ratio, that is, ~1 in the photoluminescence analysis. The growth of ZnO nanorods on stainless steel wire was governed by vapour-solid mechanism as there were no Fe particles observed at the tips of the nanorods. The photodegradation of Rhodamine B solution by ZnO nanorods followed the first-order kinetics.